Designing strip patch antennas using Matlab - Карибаев , Б.; Иманбаева, А.; Алтынбек , Т. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
The paper describes the possibility of designing antennas of any complex shape, including geometric fractals, obtaining characteristics of their electrodynamic parameters in Matlab software environment, which is used to solve technical computing problems. The objects of research were strip patch antennas based on an anisotropic fractal in two versions. The main conducting side of the first monopole antenna model under consideration in the initial zero iteration had a length of 90 mm and a width of 2 mm. In the second model, the patch antenna has been made in the form of a square, the sides of which evolve with an anisotropic fractal. The length of the sides of the square corresponding to the zero iteration is 27 mm. Their frequency-dependent electrical characteristics were obtained, in particular, the reflection coefficient S11, wave resistance (or impedance), voltage standing wave ratio (VSWR), current distribution patterns along the conductor and radiation patterns and their widths of the main lobes, gains at resonant frequencies. The results of the characteristics of the considered models were compared with the same antenna model created by the method of the last elements in the High Frequency Structural Simulator (HFSS) software environment.